Analyzing postoperative complications in colorectal cancer surgery: a systematic review enhanced by artificial intelligence - Andras, Dan; Lazar, Angela Madalina; Crețoiu, Dragoş; Berghea, Florian; Georgescu, Dragos Eugen; Grigorean, Valentin; Iacoban, Simona Raluca; Mastalier, Bogdan (Frontiers in Surgery, 2024)
IntroductionColorectal cancer stands as a predominant cause of cancer-related mortality worldwide. Despite progressive strides in surgical methodologies, the specter of postoperative complications is very large, significantly impacting both morbidity and mortality rates. This review aims to meticulously examine existing scholarly works to gauge the prevalence, severity, and therapeutic approaches to postoperative complications arising from colorectal cancer surgeries.MethodsEmploying a systematic approach, this study reviewed 135 peer-reviewed publications from the period of 2000–2023. The corpus was organized into categories reflective of the postoperative complications discussed: anastomotic leakage, port-site metastases, small bowel adhesions and obstructions, thrombosis, ileus, postoperative infections, urinary dysfunctions, and cardiovascular dysfunctions. Advanced artificial intelligence tools were leveraged for in-depth literature searches and semantic analyses to pinpoint research lacunae.ResultsThe analysis revealed that anastomotic leakage and postoperative infections garnered the majority of academic focus, representing 35% and 25% of the studies, respectively. Conversely, port-site metastases and cardiovascular dysfunctions were less frequently examined, accounting for merely 5% and 3% of the literature. The reviewed studies indicate a disparity in the reported prevalence rates of each complication, oscillating between 3% and 20%. Furthermore, the review identified a dearth of evidence-based management protocols, underscored by a pronounced heterogeneity in treatment guidelines.ConclusionsThe literature is replete with analyses on anastomotic leakage and postoperative infections; however, there exists a glaring scarcity of exhaustive research on other postoperative complications. This review emphasizes the pressing need for uniform treatment guidelines and spotlights areas in dire need of further research, aiming at the comprehensive enhancement of patient outcomes following colorectal cancer surgery.